2017
DOI: 10.1007/s00280-017-3483-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BRCA1/2 deficient ovarian cancer with CNDAC-based drug combinations

Abstract: Purpose The mechanism of action of CNDAC (2′-C-cyano-2′-deoxy-1-β-d-arabino-pentofuranosyl-cytosine) is unique among deoxycytidine analogs because upon incorporation into DNA it causes a single strand break which is converted to a double strand break after DNA replication. This lesion requires homologous recombination (HR) for repair. CNDAC, as the parent nucleoside, DFP10917, and as an oral prodrug, sapacitabine, are undergoing clinical trials for hematological malignancies and solid tumors. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
4
5
0
Order By: Relevance
“…2c) to achieve growth inhibition (Additional file 1: Table S1). Altogether, these results confirmed that OC cells with mutated BRCA1 and deficient HR-related genes are more sensitive to PARPi similarly to other studies [36, 37].
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…2c) to achieve growth inhibition (Additional file 1: Table S1). Altogether, these results confirmed that OC cells with mutated BRCA1 and deficient HR-related genes are more sensitive to PARPi similarly to other studies [36, 37].
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…The ATRX mutants also showed selective sensitivity to the toolbox ataxia telangiectasia mutated (ATM) inhibitor KU60019 and to sapacitabine, an inducer of DNA double strand breaks known to be effective in models of HR deficient cancer ( Fig. 3 b, Fig S3 e-g ) [35] . Aside from inhibitors of the DNA damage response, additional compounds identified by the screen with a high degree of preferential sensitivity in the ATRX mutants were the multi-tyrosine kinase inhibitor sunitinib [36] and, in keeping with screen 1, the HSP 90 inhibitor: 17-AAG [33] .…”
Section: Resultsmentioning
confidence: 93%
“…In addition to PARP inhibitor sensitivity, we also identify preferential sensitivity to sapacitabine in the ATRX mutated isogenic cell lines. Sapacitabine is a nucleoside analogue that induces double stranded DNA breaks, and has also been shown to be effective in other HRR deficient cancers [ 35 , 42 ]. Therefore further evaluation of this agent for ATRX mutant/deleted neuroblastoma and other HRR deficient childhood tumours is also warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected CNDAC, because, in contrast to SAMHD1 substrates such as cytarabine and decitabine, it has been proposed to be a SAMHD1 inhibitor [Hollenbaugh et al, 2017]. CNDAC is further interesting due to its unique mechanism of action among deoxycytidine analogues, which is characterised by CNDAC triphosphate (CNDAC-TP) incorporation into DNA initially causing single strand breaks and G2 cell cycle arrest [Hanaoka et al, 1999;Azuma et al, 2001;Liu et al, 2005;Liu et al, 2008;Al Abo et al, 2017;Liu et al, 2018;Liu et al, 2019].…”
Section: Introductionmentioning
confidence: 99%